Tree species diversity of ultramafic forest in Sitio Caiholo, Mt. Bahile, Puerto Princesa City, Philippines - Dela Cruz, Edwin C.; De Castro, Ma. Ellenita; Umali, Arthur Glenn A. (Journal of Degraded and Mining Lands Management, 2026)
The study assessed the tree species diversity and noteworthy floral species of an ultramafic formation at Sitio Caiholo, Mt. Bahile, Puerto Princesa City, Philippines. A 2-km modified belt transect was laid out, and a total of nine 20 m × 20 m plots were established at an interval of 250 m. Results showed that the area harbors a total of 40 morphospecies representing 36 genera and 29 families. The tree diversity may be classified as moderately low with an H’ value of 2.38, which could be attributed to the effects of ultramafic soil conditions and the severe disturbance caused by Typhoon Odette in 2022. Two newly documented species in the island of Palawan were also recorded in this study, namely Eugenia cf. tulanan, Merr., and Terminalia foetidissima Griff. On the other hand, several endemic species are also thriving in the area, namely Swintonia acuta, Engl., Colona longipetiolata Merr., Decaspermum blancoi S. Vidal, Discocalyx palawanensis Elmer ex Merr., Eugenia cf. inaequisepala Merr., Tristaniopsis littoralis (Merr.) Peter G. Wilson and J.T. Waterh, and Xanthostemon speciosus Merr. The majority of the documented species were listed as “Threatened” under the IUCN Red List (2025-2) and the Updated List of Threatened Philippine Plants and Their Categories (DAO No. 2017-11). More importantly, the area houses a number of nickel hyperaccumulator plants, which can be used in the rehabilitation and restoration of lateritic mined-out sites. These include Brackenridgea foxworthyi and Nymphanthus balgooyi, which are known to concentrate as much as 16,000 mg/kg of Ni in their dry weight tissue.